Primary endpoint results of a phase II study of vascular endothelial growth factor trap-eye in wet age-related macular degeneration - Brown, David M; Heier, Jeffrey S; Ciulla, Thomas; Benz, Matthew; Abraham, Prema; Yancopoulos, George; Stahl, Neil; Ingerman, Avner; Vitti, Robert; Berliner, Alyson J; Yang, Ke; Nguyen, Quan Dong (Ophthalmology (Rochester, Minn.), 2011)
To evaluate the biologic effects and safety of vascular endothelial growth factor (VEGF) Trap-Eye during a 12-week fixed-dosing period in patients with neovascular (wet) age-related macular degeneration (AMD). Multicenter, prospective, randomized, double-masked clinical trial with initial 12-week fixed dosing period. Data were analyzed to week 16. We included 159 patients with subfoveal choroidal neovascularization secondary to wet AMD. Patients were randomized 1:1:1:1:1 to VEGF Trap-Eye during the fixed-dosing phase (day 1 to week 12): 0.5 or 2 mg every 4 weeks (0.5 mg q4wk, 2 mg q4wk) on day 1 and at weeks 4, 8, and 12; or 0.5, 2, or 4 mg every 12 weeks (0.5 mg q12wk, 2 mg q12wk, or 4 mg q12wk) on day 1 and at week 12. The primary endpoint was change from baseline in central retinal/lesion thickness (CR/LT) at week 12; secondary outcomes included change in best-corrected visual acuity (BCVA), proportion of patients with a gain of ≥ 15 letters, proportion of patients with a loss of >15 letters, and safety. At week 12, treatment with VEGF Trap-Eye resulted in a significant mean decrease in CR/LT of 119 μm from baseline in all groups combined (P<0.0001). The reduction in CR/LT with the 2 mg q4wk and 0.5mg q4wk regimens was significantly greater than each of the quarterly dosing regimens. The BCVA increased significantly by a mean of 5.7 letters at 12 weeks in the combined group (P<0.0001), with the greatest mean gain of >8 letters in the monthly dosing groups. At 8 weeks, BCVA improvements were similar with 2 mg q4wk and 2 mg q12wk dosing. After the last required dose at week 12, CR/LT and visual acuity were maintained or further improved at week 16 in all treatment groups. Ocular adverse events were mild and consistent with safety profiles reported for other intraocular anti-VEGF treatments. Repeated monthly intravitreal dosing of VEGF Trap-Eye over 12 weeks demonstrated significant reductions in retinal thickness and improvements in visual acuity, and was well-tolerated in patients with neovascular AMD. Proprietary or commercial disclosure may be found after the references.